Portable environment monitoring system based IOT / Siti Zulaikha Mohd Dusuki - Mohd Dusuki, Siti Zulaikha (2024)
Air contains many types of particles such as gas, dust, microorganisms, etc. The air is considered in normal condition when the percentage of certain gases are reached such as 78% consisted of nitrogen gas, 21% consisted of oxygen gas, 0.97% for the carbon dioxide while the other gas makes up 0.03%. A monitoring system can be used to observe the data collected in the environment. It can be used to monitor any projectspecific data, including temperature, sand moisture, humidity, and air quality. In this project, the monitoring system is measured using the air quality, temperature, and humidity. Looking back, some people were not aware that hazardous fumes were there because they could not be seen with the naked eye in some cases. When in touch with the harmful gas, the scenario may have an impact on the skin and respiratory system. This study attempts to create an Internet-connected microcontroller called Arduino UNO that can detect air quality. Additionally, the goal of this project is to develop an Internet of Things (IoT)-based mobile phone-based portable environment monitor system. The MQ-135 gas sensor, MQ-2 gas sensor, and DHT22 sensor provide the input. In order to warn the user to be more aware and take further action, this system will help the air quality monitoring to be more effective to the people's interior and outdoor area